Technology Enhanced Learning: The Role of Ontologies for Feedback in Music Performance - Yee-King, Matthew John; Wilmering, Thomas; Rodriguez, Maria Teresa Llano; Krivenski, Maria; d'Inverno, Mark (Frontiers in Digital Humanities, 2019)
In this paper, we present an analysis of feedback as it occurs in classroom-based and technology supported music instrument learning. Feedback is key to learning in music education, and we have developed technology based on ideas from social media and audio annotation which aims to make feedback more effective. The analysis here aims to enhance our understanding of technology-mediated feedback. The result of this analysis is three ontologies describing feedback and feedback systems. First, we developed the teacher's ontology using a qualitative, observational approach to describe the types of feedback that music instrument tutors give to their students. We used this ontology to inform the design of an online music annotation platform for music students. Second, we developed the grounded ontology using a grounded theory approach, based on 2,000 annotations made by students and tutors using the annotation platform. We compare the grounded and teacher's ontologies by examining structural, semantic and expressive features. Through this comparison, we find that the grounded ontology includes elements of the teacher's ontology as well as elements relating to practical and social aspects of the annotation platform, while the teacher's ontology contains more domain knowledge. The third ontology is a formalisation of the transactional capabilities of the platform, and we refer to it as the platform ontology. We present it using the OWL language, and we show how this allows us to develop several practical use cases, including the use of semantic web capabilities in music education contexts.